Diet and chemical defenses of the Sonoran Desert toad - Marina D. Luccioni; Jules T. Wyman; Edgard O. Espinoza; Lauren A. O’Connell (PLoS ONE, 2025)
The Sonoran Desert toad ( Incilius alvarius ) is the only animal known to secrete the psychedelic compound 5-MeO-DMT as a chemical defense, but the source of 5-MeO-DMT in I. alvarius remains unknown. Some amphibians produce chemical defenses endogenously or through symbiotic interactions, while others acquire them from specialized diets. In this study we analyzed toxin gland secretions and diet profiles from wild I. alvarius and sympatric anurans from native and urban habitats around Tucson, Arizona to explore possible links between diet and 5-MeO-DMT production. All I. alvarius secreted high concentrations of 5-MeO-DMT, whereas other sympatric toads did not. The diet of I. alvarius was similar to that of sympatric anurans, indicating that I. alvarius does not exhibit relative dietary specialization. We found slight dietary differences between I. alvarius in native and urbanized habitats. Taken together, these lines of evidence suggest that diet is not directly linked to 5-MeO-DMT production and support the alternative hypotheses that I. alvarius synthesizes 5-MeO-DMT endogenously or via a microbial symbiont.